Ukrainian Scientific Research Institute of Economics and Agriculture Organization: first scientific report (1928–1929) - Zosimov, I. A. (History of science and technology, 2016)
The publication explores the first scientific report of the Ukrainian Scientific Research Institute of Economics and Agriculture Organization for 1928–1929. It functioned in 1928–1937, but there are no materials about its scientific activity. The report is presented in the publications in the periodical «Journal of Agricultural Science and Experiential Deed» and archival institutions in Ukraine.